Soft, Sharp, and Evil Power: The Russian Orthodox Church in the Russian Invasion of Ukraine - Kilp, Alar (Occasional papers on religion in Eastern Europe, 2022)
This paper examines the enactment of soft/sharp/evil power by the Russian Orthodox Church and its leaders during a month before the major exertion of hard power by the Russian military and one month after the invasion of Ukraine. In the period from January 25 until March 25, 2022, 27 messages of the leading actors in the Church-Patriarch Kirill and Metropolitan Hilarion, head of the Department of External Church Relations (DECR)-are closely examined. The results are presented and discussed in four thematic sections: 1) soft power: the religious approach to the Russian World; 2) Sharp power: the territorial expansion of the Church with the help of the Russian state; 3) Evil power: Church leaders on war and peace; 4) Comparison with the messages of Russian political leaders (President Vladimir Putin and Foreign Minister Sergei Lavrov). The soft power the Russian Church exercises for the benefit of Russian foreign relations is manifest in the strong emphasis on the spiritual unity of Russian and Ukrainian people within the religious narrative of the Russian World. This soft power takes the form of sharp power vis-à-vis the Ukrainian invasion and vis-à-vis those, who recognize the autocephalous Orthodox Church of Ukraine. The influence of the Russian Church in support of the Russian government’s invasion has also a dimension of evil power, that is, power exercised in service to immoral or unethical state actions such as the unwarranted invasion of Ukraine by Russian military forces. Finally, both religious and political leaders are similar in denying the agency (including autonomous existence) of the nation-state and the Orthodox Church of Ukraine, they consider both the Orthodox Church of Ukraine and post-2014 Ukrainian government to be tools of outside forces (be it the West, the United States, or the Ecumenical Patriarch), and they threaten and attempt to punish everyone who supports those whom they have selected out as targets.